Bader A.

asked • 02/11/18

What is ∫-7^-1 f(x)dx?

suppose that f(x) is an even function and let ∫0^1 f(x)dx = 5 and ∫0^7 f(x)dx = 1. What is ∫-7^-1 f(x)dx?
 
This is my work
 
I expand ∫-7^-1 f(x)dx to F(-1) - F(-7)
 
F(-1) - F(-7) is the same thing as F(1) - F(7) since it is an even function
 
plug in the values to get 5-1, which equals 4
 
I strongly believe that the answer is 4, however, on the test my teacher is saying it's -4. I talked to her about it and she did not listen. Could someone show me if I am right, or if the answer is indeed -4?
 
Also, I wasn't really sure how to write the definite integral on the keyboard, so if you didn't get what I mean by ∫-7^-1, I meant to say that the lower limit is -7 and the upper limit is -1

2 Answers By Expert Tutors

By:

Bobosharif S. answered • 02/11/18

Tutor
4.4 (32)

PhD in Math, MS's in Calulus

Arturo O.

The integral of an ODD function over a balanced interval is zero.  Example:
 
-11 xdx = 0
 
But the integral of an EVEN function over a balanced interval gives twice the integral from 0 to the upper limit.  Example:
 
-11 x2dx = (x3/3)|-11 = 1/3 - (-1/3) = 2/3 = 2∫0x2dx
 
 
Report

02/11/18

Arturo O.

Therefore, since f(x) is even,
 
-77 f(x)dx = 2∫07 f(x)dx
Report

02/11/18

Bobosharif S.

Yes, right. I messed up.. Thanks
Report

02/11/18

Arturo O.

No problem.  Thank you for your many fine solutions.
Report

02/11/18

Bobosharif S.

Since f(x) is even ∫-77f(x)dx=2∫07f(x)dx=2.

2=∫-77f(x)dx=(∫-7-1+∫-10+∫07)f(x)dx= ∫-7-1f(x)dx+∫-10f(x)dx+1.
5=∫01f(x)dx=-∫-10f(-x)dx=-∫-10f(x)dx. ⇒∫-10f(x)dx=-5
-7-1f(x)dx=2+4=6.
Please disregard the previous answer. Thanks to Arturo O. I corrected my mistake. But there might be still some mistakes. Therefore, it would be goo to look through carefully.
 
Report

02/11/18

Arturo O.

Let us work this very carefully step by step.
 
f(x) is even, so
 
-70 f(x)dx = ∫07 f(x)dx = 1
 
and
 
-10 f(x)dx = ∫01 f(x)dx
 
But
 
-70 f(x)dx = ∫-7-1 f(x)dx + ∫-10 f(x)dx ⇒
 
07 f(x)dx = ∫-7-1 f(x)dx + ∫01 f(x)dx ⇒
 
1 = ∫-7-1 f(x)dx + 5 ⇒
 
-7-1 f(x)dx = 1 - 5 = -4
 
The teacher is correct.
Report

02/11/18

Bobosharif S.

You are absolutely right!  I messed it up for the second time.
Thank you Arturo!. You saved my life more twice.
Report

02/11/18

Bobosharif S.

To Bader from Scottsdale, AZ. Please disregard my answer and my comment above. They both were wrong!  
Report

02/11/18

Bader A.

Thank you guys, I now understand why the answer is -4
Report

02/11/18

Bobosharif S.

We have to thank Arturo O.!
Report

02/11/18

Arturo O. answered • 02/11/18

Tutor
5.0 (66)

Experienced Physics Teacher for Physics Tutoring

Bader A.

I'm sorry for the confusion that I caused. What I meant is what is ∫a=-7 b=-1 f(x)dx, when f(x) is an even function, ∫a=0 b=1 f(x)dx=5 and ∫a=0 b=7 f(x)dx=1
Report

02/11/18

Arturo O.

If f(x) is even, then its integral F(x) is odd.  The indefinite integral of an even function is always an odd function, and the indefinite integral of an odd function is always an even function.  Your mistake was to assume that F(-1)-F(-7) is the same thing as F(1)- F(7).  It is true that
 
f(-x) = f(x),
 
since f(x) is even.  But its' indefinite integral F(x) is odd, so
 
F(-x) = -F(x).
 
Therefore 
 
F(-1) - F(-7) = -F(1) -[-F(7)] = F(7) - F(1).
 
I think you have what you need to figure it out now.
Report

02/11/18

Still looking for help? Get the right answer, fast.

Ask a question for free

Get a free answer to a quick problem.
Most questions answered within 4 hours.

OR

Find an Online Tutor Now

Choose an expert and meet online. No packages or subscriptions, pay only for the time you need.